Infrastructure Availability for the Care of Congenital Heart Disease Patients and Its Influence on Case Volume, Complexity and Access Among Healthcare Institutions in 17 Middle-Income Countries. Issue 1 (21st October 2021) - Wamala, Isaac; Gongwer, Russell; Doherty-Schmeck, Kaitlin; Jorina, Maria; Betzner, Anne; Zheleva, Bistra; Gauvreau, Kimberlee; Baird, Christopher W.; Jenkins, Kathy
The care for patients with congenital heart disease (CHD) is multi-disciplinary and resource intensive. There is limited information about the infrastructure available among programs that care for CHD patients in low and middle-income countries (LMIC). A survey covering the entire care-pathway for CHD, from initial assessment to inpatient care and outpatient follow-up, was administered to institutions participating in the International Quality Improvement Collaborative for Congenital Heart Disease (IQIC). Surgical case complexity-mix was collected from the IQIC registry and estimated surgical capacity requirement was based on population data. The statistical association of selected infrastructure with case volume, case-complexity and percentage of estimated case-burden actually treated, was analyzed. Thirty-seven healthcare institutions in seventeen countries with median annual surgical volume of 361 (41–3503) operations completed the survey. There was a median of two (1–16) operating room/s (OR), nine (2–80) intensive care unit (ICU) beds, three (1–20) cardiac surgeons, five (3–30) OR nurses, four (2–35) anesthesiologists, four (1–25) perfusionists, 28 (5–194) ICU nurses, six (0–30) cardiologists and three (1–15) interventional cardiologists. Higher surgical volume was associated with higher OR availability (p = 0.007), number of surgeons (p = 0.002), OR nurses (0.008), anesthesiologists (p = 0.04), perfusionists (p = 0.001), ICU nurses (p < 0.001), years of experience of the most senior surgeon (p = 0.03) or cardiologist (p = 0.05), and ICU bed capacity (p = 0.001). Location in an upper-middle income country (P = 0.04), OR availability (p = 0.02), and number of cardiologists (p = 0.004) were associated with performing a higher percentage of complex cases. This study demonstrates an overall deficit in the infrastructure available for the care of CHD patients among the participating institutions. While there is considerable variation across institutions surveyed, deficits in infrastructure that requires long-term investment like operating rooms, intensive care capacity, and availability of trained staff, are associated with reduced surgical capacity and access to CHD care.